Interrole conflict and social support : a study of married women nurses - Wong, Yuet Chee (1997)
The study focused on inter-role conflict and social support. The first objective of this study was to determine the intensity of inter-role conflict experienced by married women nurses in their total life space as they performed their multiple roles. Secondly, it examined the potential sources of social support they managed to gamer from individuals within and without the work place in times of work-family conflict: spouse, friends and relatives, co-worker and boss/supervisor.The sample size of 129 respondents was taken from the population of 615 eligible nurses meeting the criteria for the study. All instruments used were from previously developed instruments and adaptations of the instruments. Data collected from self-administered questionnaires were used to examine the work-family interface environment among the respondents. The results showed that medium inter-role conflict intensities were experienced by majority of the nurses. The nurses received the highest amount of support from their spouses and the least from their bosses/supervisors. It is implied that social support could have been an important factor in reducing the level of experienced work-family conflict among the nurses.